Do czego służą badania na stałych powierzchniach w Białowieskim Parku Narodowym? - Bobiec, Andrzej (Leśne Prace Badawcze, 2016)
The purpose of the strictly protected area of the Białowieża National Park (BNP) established in early 1900s, was to protect a compact block of the Białowieża forest from any direct human influence and activity. Its founders considered it a „laboratory of nature.” In 1936, five rectangular plots with a total area of ca. 15.5 ha (ca. 0.3% of the BNP) were set up for regular monitoring of stand development with regards to the initial state and variability of soil conditions. During the first 76 years of the project, a steady increase in the proportion of hornbeam and lime tree at the expense of shade-intolerant species was observed. This trend has been interpreted by the researchers involved in the monitoring of the permanent BNP plots to constitute a biodiversity-threatening development caused by preservation efforts. Such an interpretation has been widely incorporated in the public debate by political authorities and the forestry sector. In this critical article I challenge the major arguments presented by the key expert in silviculture, prof. B. Brzeziecki. My criticism is directed at the methodological approach as well as at the data interpretation.